Structural Health Monitoring 2015 2015
DOI: 10.12783/shm2015/26
|View full text |Cite
|
Sign up to set email alerts
|

Bondline Integrity Monitoring of Adhesively Bonded Structures via an Electromechanical Impedance Based Approach

Abstract: Bondline integrity is still one of the most critical concerns in the design of aircraft structures up to date. Due to the lack of confidence on the integrity of the bondline both during fabrication and service, the industry standards and regulations require assembling the composites using the inefficient "black-aluminum" approach, i.e. drill holes and use fasteners. Furthermore, current state-of-the-art non-destructive evaluation (NDE) and structural health monitoring (SHM) techniques are incapable of offering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…where I l is the current injected into the l th electrode, V l is the boundary voltage collected while I l is being injected, and z l is the contact impedance of the lth electrode. Equations (11), (13), and (14) constitute the equations to be solved via FE analysis. Instead of solving for the actual conductivity, a one-step inverse calculation was adopted from Alder and Guardo 36 to estimate the change in conductivity before and after the load.…”
Section: Eitmentioning
confidence: 99%
“…where I l is the current injected into the l th electrode, V l is the boundary voltage collected while I l is being injected, and z l is the contact impedance of the lth electrode. Equations (11), (13), and (14) constitute the equations to be solved via FE analysis. Instead of solving for the actual conductivity, a one-step inverse calculation was adopted from Alder and Guardo 36 to estimate the change in conductivity before and after the load.…”
Section: Eitmentioning
confidence: 99%
“…[1,2], (ii) sense their flight and aeroelastic state (airspeed, angle of attack, flutter, stall, aerodynamic loads, etc.) and internal structural condition (stresses, strains, damage) [3,4], and (iii) effectively interpret the sensing data to achieve real-time state awareness and health monitoring [5][6][7][8][9][10][11][12]. Towards this end, novel data-driven approaches are needed for the accurate interpretation of sensory data collected under varying flight states, structural conditions, and uncertainty in complex dynamic environments.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, 3133 the authors and co-workers addressed the problem of bondline integrity monitoring via the use of piezoelectric transducers embedded inside adhesively bonded lap joints and monitoring the EMI signatures. The problem was tackled via an EMI-based cross-correlation approach 31 and a preliminary approach based on the use of EMI-based damage indices.…”
Section: Introductionmentioning
confidence: 99%
“…The problem was tackled via an EMI-based cross-correlation approach 31 and a preliminary approach based on the use of EMI-based damage indices. 32,33 In these studies, the changes in the EMI with respect to static loading conditions showed significant potential in successfully diagnosing the degradation of the bondline. Therefore, this study aims at the postulation and extended experimental assessment and evaluation of an EMI-based method for monitoring the integrity of adhesively bonded structures.…”
Section: Introductionmentioning
confidence: 99%